PENGARUH LINGKUNGAN KERJA, KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI UNIT USAHA HUNIAN, GEDUNG, AGRIBISNIS DAN TAMAN BADAN USAHA FASILITAS DAN LINGKUNGAN PADA BADAN PENGUSAHAAN BATAM - Septa Diana Nabella; Sumardin (Postgraduate Management Journal, 2021)
The regression coefficient is significant or the Work Environment variable has an effect on Employee Work Productivity. The regression coefficient is significant or the Job Satisfaction variable affects the Employee Productivity variable. The regression coefficient is significant or the Work Discipline variable has an effect on the Employee Work Productivity variable. Anova test produces a calculated F number of 120.798> F table 2.74 with a significance level (probability number) of 0.05. F count> F table then Ho is rejected and H1 is accepted. Then the regression coefficient of Work Environment (X1), Job Satisfaction (X2) and Work Discipline (X3) together have a significant effect on the Employee Work Productivity variable (Y) in Residential Business Units, Buildings, Agribusiness and Business Entity Parks Facilities and Environment in BP Batam..